Kajian Rekayasa Lalulintas (Pemberlakuan Jalan Satu Arah Jln. Dr. Wahidin Ruas Rembiga – Gunung Sari) Pada Simpang Empat Rembiga Kota Mataram - Addinuri Addinuri; Titik Wahyuningsih; Anwar Efendy (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Indonesia is one of the developing countries where cases are more complex than developed countries, one of which is traffic jams that we often encounter in some cities, one of which is Mataram City, resulting in an increase in the number of traffic movements of various types of vehicles, increasing the density of intersection traffic flows and the need for traffic management. the right way to regulate the smooth flow of traffic, aims to determine the performance of the intersection and the application of one-way traffic engineering on Jalan Dr. Wahidin Rembiga - Mataram City, which has quite severe congestion due to inadequate road width, is a connecting road between cities and regencies, resulting in an increase in the number of diverse movements of various types of vehicles. The application of the one-way road system as a solution to overcome congestion. Each segment has a different road width and shoulder width. using the 1997 MKJI guide (Indonesian Road Capacity Manual). The main factors as research parameters are the degree of saturation and the level of segment service. The results of the level of service performance are very clear on the Jalan Dr. Wahidin when the existing condition obtained a degree of saturation value of 1.13, it means that the service level of the segment gets an F value, the implementation of a one-way system, the degree of saturation drops to 0.52, the level of service changes to C which is very influential on road service and overcomes congestion on the road.